Individual differences in social homeostasis - Bales, Karen L.; Hang, Sally; Paulus, John P.; Jahanfard, Elaina; Manca, Claudia; Jost, Geneva; Boyer, Chase; Bern, Rose; Yerumyan, Daniella; Rogers, Sophia; Mederos, Sabrina L. (Frontiers in Behavioral Neuroscience, 2023)
The concept of “social homeostasis”, introduced by Matthews & Tye in 2019, has provided a framework with which to consider our changing individual needs for social interaction, and the neurobiology underlying this system. This model was conceived as including detector systems, a control center with a set point, and effectors which allow us to seek out or avoid additional social contact. In this paper, we review and theorize about the many different factors that might contribute to the set point of a person or animal, including individual, social, cultural, and other environmental factors. We conclude with a consideration of the empirical challenges of this exciting new model.